Hereditary angioedema: epidemiology, management, and role of icatibant - Ghazi A (Dove Medical Press, 2013)
Aasia Ghazi, J Andrew GrantUniversity of Texas Medical Branch, Division of Allergy and Clinical Immunology, Galveston, TX, USAAbstract: Hereditary angioedema (HAE) is an autosomal dominant, potentially life-threatening condition, manifesting as recurrent and self-limiting episodes of facial, laryngeal, genital, or peripheral swelling with abdominal pain secondary to intra-abdominal edema. The estimated prevalence of HAE in the general population is one individual per 50,000, with reported ranges from 1:10,000 to 1:150,000, without major sex or ethnic differences. Various treatment options for acute attacks and prophylaxis of HAE are authorized and available in the market, including plasma-derived (Berinert®, Cinryze®, and Cetor®) and recombinant (Rhucin® and Ruconest™) C1 inhibitors, kallikrein inhibitor-ecallantide (Kalbitor®), and bradykinin B2 receptor antagonist-icatibant (Firazyr®). Some of these drugs are used only to treat HAE attacks, whereas others are only approved for prophylactic therapies and all of them have improved disease outcomes due to their different mechanisms of action. Bradykinin and its binding to B2 receptor have been demonstrated to be responsible for most of the symptoms of HAE. Thus icatibant (Firazyr®), a bradykinin B2 receptor antagonist, has proven to be an effective and more targeted treatment option and has been approved for the treatment of acute attacks of HAE. Rapid and stable relief from symptoms of cutaneous, abdominal, or laryngeal HAE attacks has been demonstrated by 30 mg of icatibant in Phase III clinical trials. Self-resolving mild to moderate local site reactions after subcutaneous injection of icatibant were observed. Icatibant is a new, safe, and effective treatment for acute attacks of HAE. HAE has been reported to result in enormous humanistic burden to patients, affecting both physical and mental health, with a negative impact on education, career, and work productivity, and with substantial economic burdens. The timely and proper use of disease-specific treatments could improve patients' quality of life, reduce the disease-specific morbidity and mortality, and, last but not least, reduce costs associated with hospitalizations and emergency room visits. Therefore, the paradigm of HAE treatment has the potential to evolve significantly, thereby exponentially improving a patient’s quality of life.Keywords: hereditary angioedema, icatibant, C1 inhibitor, bradykinin